Income, Population and Migration Flows in the 21st Century - A Societal Challenge for Europe - Docquier , Frédéric; Machado , Joël (Studia Oeconomica Posnaniensia, 2026)
Since World War II immigration rates have dramatically increased in highincome countries, and the control of immigration has become a major policy issue. This paper provides worldwide projections for international migration flows in the 21st century. To do so, we develop and parametrize a dynamic, stylized model of the world economy that accounts for the complex interactions between population growth, the evolution of educational attainment, income disparities and migration flows. Our baseline scenario extrapolates the historical trends in TFP (total factor productivity) disparities and matches this against the ’high-fertility’ population prospects of the United Nations. Under this scenario, the demographic share of Africa and the income gap between Africa and high-income countries will dramatically increase during the 21st century. We predict that immigration rates will remain stable in most high-income countries, except the fifteen members of the European Union (EU15), where the average proportion of immigrants will rise from 7,5 to 17,2 percent. We then assess the sensitivity of our projections to changes in migration policies in other regions, TFP disparities, fertility, and education policies in developing countries. The rise in European migration pressure could be alleviated if Africa takes off economically or restrains its population growth rates. However, our qualitative predictions for future migration flows hold in all scenarios.